1997
DOI: 10.1063/1.475088
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon spectroscopy of the low lying Rydberg states of NO. II. Application to the NO–Ar complex

Abstract: Two-photon spectroscopy of the low lying Rydberg states of NO. I. The 3p and 3d complexes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 71 publications
6
38
0
Order By: Relevance
“…Knowing the source of each spectral component allows insight into the assignment of the spectrum, and indicates that significant stretch/bend mixing occurs, even early on in the spectrum, while slightly higher in energy various Fermi resonance interactions are likely occurring, causing further mixing. The overall appearance of the NO-Ar and NO-Kr simulated spectra is similar to that achieved in earlier work by Mack et al 21 which were obtained employing the model of Meyer, 22 where the two-photon intensity was included explicitly. As noted previously, 1 we take this to imply that the explicit inclusion of the two-photon intensities is not required for this level of agreement.…”
Section: Final Remarkssupporting
confidence: 71%
See 4 more Smart Citations
“…Knowing the source of each spectral component allows insight into the assignment of the spectrum, and indicates that significant stretch/bend mixing occurs, even early on in the spectrum, while slightly higher in energy various Fermi resonance interactions are likely occurring, causing further mixing. The overall appearance of the NO-Ar and NO-Kr simulated spectra is similar to that achieved in earlier work by Mack et al 21 which were obtained employing the model of Meyer, 22 where the two-photon intensity was included explicitly. As noted previously, 1 we take this to imply that the explicit inclusion of the two-photon intensities is not required for this level of agreement.…”
Section: Final Remarkssupporting
confidence: 71%
“…We investigated this and it seemed that some of the experimental features to the red of the main bands could be attributable to hot features; however, it was not possible to be conclusive on this as the match in intensities was not overwhelmingly convincing. The experimental REMPI spectrum was mass-resolved and is of the NO-20 Ne isotopologue-it was found that the spectrum of the isotopologue NO- 22 Ne was identical within the experimental resolution. 20 We also note that in Ref.…”
Section: No-nementioning
confidence: 99%
See 3 more Smart Citations